Linking Genes and Political Orientations: Testing the Cognitive Ability as Mediator Hypothesis. Issue 6 (18th August 2014) - Oskarsson, Sven; Cesarini, David; Dawes, Christopher T.; Fowler, James H.; Johannesson, Magnus; Magnusson, Patrik K. E.; Teorell, Jan
Abstract : Recent research has demonstrated that genetic differences explain a sizeable fraction of the variance in political orientations, but little is known about the pathways through which genes might affect political preferences. In this article, we use a uniquely assembled dataset of almost 1, 000 Swedish male twin pairs containing detailed information on cognitive ability and political attitudes in order to further examine the genetic and environmental causes of political orientations. Our study makes three distinct contributions to our understanding of the etiology of political orientations: (1) we report heritability estimates across different dimensions of political ideology; (2) we show that cognitive ability and political orientations are related; and (3) we provide evidence consistent with the hypothesis that cognitive ability mediates part of the genetic influence on political orientations. These findings provide important clues about the nature of the complex pathways from molecular genetic variation to political orientations.